Expression and structural analysis of taste receptor genes in Iberian and Duroc pigs - Cristina Óvilo; Rita Benítez; Yolanda Núñez; Ramón Peiró-Pastor; Fabian García; Eduardo De Mercado; Emilio Gómez-Izquierdo; Juan García-Casco; Clemente López-Bote; María Muñoz (Genetics Selection Evolution)
Abstract Background Taste receptor genes are expressed in sensory cells located in the tongue and influence food preferences, voluntary feed intake, and other relevant traits. Taste perception may differ between livestock breeds that show differences in eating behaviour and between animals that receive different diets or show phenotypic variation in feed intake or related-traits. The objectives of this work were to deepen the understanding of the regulation of the function of taste receptor genes in the circumvallate papillae of obese Iberian pigs in comparison to Duroc pigs, and to characterize their genetic variation and associations with relevant production traits. Results We performed a gene expression and structural analysis of ten taste receptor genes in Iberian and Duroc pigs. Gene expression was quantified in the circumvallate papillae of 48 growing Iberian and Duroc pigs maintained under identical management conditions but fed isocaloric diets differing in energy source: either high concentration of fat rich in oleic acid (HO) or carbohydrates (CH); and sacrificed after 47 days of treatment (50.5 kg live weight). Gene expression differed between the two breeds for most of the analyzed genes, with the TAS1R1, TAS1R2, TAS1R3, TAS2R4, TAS2R38, TAS2R39, GPR84, and CD36 genes being overexpressed in Duroc pigs. The diet effect was modulated by breed, with TAS1R1, TAS1R3, and TAS2R4 genes being overexpressed only in Duroc pigs fed the HO diet. Detection of genetic variants (single nucleotide polymorphisms, SNPs) for this panel of genes was performed on muscle RNA-seq data, and three SNPs in the TAS1R1, TAS1R3, and CD36 genes were selected for association studies. All three SNPs were associated with various growth, fattening, tissue fat content, and composition traits. Moreover, the CD36:c.910G/T SNP was associated with oral CD36 gene expression and with differences in the predicted mRNA secondary structure. Conclusions Most taste receptor genes are expressed at lower level in circumvallate papillae from Iberian than Duroc pigs. This aligns with lower overall taste sensitivity, higher feed intake, and obese nature of Iberian pigs. Significant association results were observed for SNPs in the TAS1R1 and TAS1R3 genes with meat quality traits and liver composition, which showed segregation in world-wide distributed breeds, but particularly for a potential causal SNP in the CD36 gene, associated with growth and tissue composition, which segregates in Iberian populations.